Hyoid Bone Position in Patients with and without Temporomandibular Joint Osteoarthrosis: A Cone-Beam Computed Tomography and Cephalometric Analysis. (11th December 2021) - Zhou, Xueman; Xiong, Xin; Yan, Zhebin; Xiao, Chuqiao; Zheng, Yingcheng; Wang, Jun
Abstract : Objective . To assess the differences in hyoid bone position in patients with and without temporomandibular joint osteoarthrosis (TMJOA). Methods . The present cross-sectional study was conducted in 427 participants whose osseous status was evaluated using cone-beam computed tomography and classified into normal, indeterminate osteoarthrosis (OA), and OA. The hyoid bone position and craniofacial characteristics were evaluated using cephalograms. Patients were divided into the normal group ( N  = 89), indeterminate OA group ( N  = 182), and OA group ( N  = 156). Descriptive statistics, one-way analysis of variance, and age- and sex-based stratified analyses were performed. P < 0.05 was considered statistically significant. Results . The differences in Hy to MP, Hy-RGn, Hy to C3-RGn, C3-RGn, and Go-Hy-Me among the three groups were statistically significant. The differences in the Frankfort-mandibular plane angle, saddle angle, articular angle, gonial angle, ramus height, and posterior facial height were statistically significant. After adjusting age and sex, the Hy-RGn and C3-RGn in the normal group were significantly greater than the OA group. No statistical differences were observed in the hyoid measurements in the stratified analyses in males or subjects less than 18 years old. The differences in Hy to MP, Hy to C3-RGn, and Go-Hy-Me in female patients among the three groups were statistically significant. The differences in Hy to SN, Hy to FH, Hy to PP, Hy to MP, Hy-RGn, Hy-C3, Hy to C3-RGn, Go-Hy-Me, Hy-S, and C3-Hy-S in adults were statistically significant. Conclusion . The differences in the hyoid bone position, mainly relative to the mandible, were statistically significant in patients with or without TMJOA. The difference pattern varied among different age and sex groups. Clinical evaluation of the hyoid position must consider the age and sex of patients. Longitudinal studies are required to clarify the causal relationship between TMJOA and hyoid bone position.